2022
DOI: 10.26434/chemrxiv-2022-pf8k0
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Degradable Vinyl Polymer Nanoparticles/Latexes by Aqueous Nitroxide-Mediated Polymerization-Induced Self-Assembly

Abstract: The synthesis of degradable vinyl polymer nanoparticles/latexes in aqueous dispersed media is receiving much attention, particularly for biomedical applications and plastic pollution control, as it can circumvent the severe limitations associated with emulsification of preformed degradable polymers. Polymerisation-induced self-assembly (PISA), which enables the in-situ formation of aqueous suspensions of diblock copolymer nano-objects of high solids content, has become a very popular polymerization process due… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…License: CC BY-NC-ND 4.0 3 accessing a diverse range of polymeric nanoparticles (NPs) with various morphologies and sizes. [1][2][3][4][5][6][7] These methodologies address significant barriers to scaling up traditional self-assembly procedures, enabling the streamlined synthesis of concentrated polymeric NP dispersions with typical solids content (SC%) ranging from SC% = 25 -50 w%. Reversible additionfragmentation chain transfer (RAFT) dispersion polymerization have been extensively investigated yielding detailed phase diagrams for many systems.…”
Section: Introductionmentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 3 accessing a diverse range of polymeric nanoparticles (NPs) with various morphologies and sizes. [1][2][3][4][5][6][7] These methodologies address significant barriers to scaling up traditional self-assembly procedures, enabling the streamlined synthesis of concentrated polymeric NP dispersions with typical solids content (SC%) ranging from SC% = 25 -50 w%. Reversible additionfragmentation chain transfer (RAFT) dispersion polymerization have been extensively investigated yielding detailed phase diagrams for many systems.…”
Section: Introductionmentioning
confidence: 99%
“…6 copolymerization of n-butyl acrylate and styrene with up to 2 mol % DOT. 15 Atom-transfer radical polymerization (ATRP) 16 is, arguably, more complex than RAFT polymerization. 17 However, it has a distinct advantage over (thermally initiated) RAFT in that it does not require a radical initiator (such as AIBN).…”
Section: ■ Introductionmentioning
confidence: 99%
“…RDRP of thionolactones has been achieved exclusively through RAFT polymerization with which TARO radical polymerization appears to be fully compatible. During the writing of this article, Lages et al reported the successful nitroxide-mediated copolymerization of n -butyl acrylate and styrene with up to 2 mol % DOT …”
Section: Introductionmentioning
confidence: 99%
“…During the writing of this manuscript, Lages et al reported the successful nitroxide-mediated copolymerization of n-butyl acrylate and styrene with up to 2 mol-% DOT. 15 Atom transfer radical polymerization 16 is, arguably, more complex than RAFT polymerization. 17 But it has a distinct advantage over (thermally initiated) RAFT in that it does not require a radical initiator (such as AIBN).…”
Section: Introductionmentioning
confidence: 99%